Angiographic characteristics of contralateral asymptomatic eyes in acute Central serous chorio-retinopathy in an Asian population - Gurung, Rajya L; Anwar, Afaque (Asian Journal of Medical Sciences, 2018)
Background: Acute Central serous chorioretinopathy (CSCR) is characterised by an idiopathic circumscribed serous retinal detachment, usually confined to the central macula. Aims and Objective: We aimed to analyse the angiographic characteristics of contra-lateral asymptomatic eyes of patients presenting with acute CSCR in an Asian population. Materials and methods: This is a retrospective study of 70 consecutive patients presenting with acute CSCR who underwent detailed fundus evaluation and fluorescein angiography within 1 year period. Results: Fluorescein angiograms of 70 patients were analysed . Male to female ratio was 10.66 : 1. The age range of patients was ( 24-54 ) years , median 37 years and mean age 38.37 years with standard deviation 6.78 . Active tobacco use was found in 34 (48.6%) eyes and systemic steroid use in 2 (2.8%) eyes. Majority, 48 (34.3% ) of symptomatic and all 70(100% ) of contralateral asymptomatic eyes had presenting best corrected visual acuity ( BCVA ) of ≥ 20/60. All 70 (100%) of symptomatic eyes had angiographic evidence of leakage in comparison to only 25(35.7%) of contralateral asymptomatic eyes. Multi-focal leakage was seen in 21 (30%) of symptomatic eyes and 6(8%) of asymptomatic eyes , inkblot leakage pattern being the most common in seen in 57 (81.4%) of symptomatic and 16 (22.8%) of asymptomatic eyes. The most common site of leakage was central seen in 62 (88.5%) of symptomatic eyes and 19 (27.1%) of contralateral asymptomatic eyes. Conclusion: The findings in our study was comparable to other Asian studies. A considerable number of patients had angiographic evidence of CSCR in the contralateral asymptomatic eye.